Análisis del equilibrio trabajo-vida en servidoras de la secretaría de gestión y desarrollo de pueblos y nacionalidades en la provincia de Pichincha - Intriago Zambrano, María Victoria (2025)
The aim of this study was to analyze the work-life balance of female public servants at the Secretariat for the Management and Development of Peoples and Nationalities of Pichincha (SGDPN), in order to propose improvement strategies that support their occupational and personal well-being. A non-experimental study was conducted, evaluating a non-probabilistic sample of 32 female public servants from the aforementioned institution. The descriptive method was used to characterize the regulatory framework, and data collection techniques included interviews and a structured survey using the Survey Work-Home Interaction Nijmegen (SWING) questionnaire. The survey was rated using a 4-point Likert scale and validated with Cronbach’s Alpha coefficient. For the development of improvement strategies, the 5W+1H matrix was applied. The findings reveal that the current regulatory framework addresses only certain aspects of work-life balance, and there are gaps in the implementation of institutional policies at some operational levels. Additionally, there is cultural and institutional resistance, associating flexibility with reduced productivity. The SWING questionnaire results indicated a moderate imbalance in work-life interaction, with work-to-life and life-to-work interferences occurring equally, in both positive and negative ways. If these inconsistencies persist, they may negatively impact both the well-being of female public servants and the institutional efficiency of the SGDPN. Therefore, the study urges the consideration of the proposed improvement strategies.